EFFICIENCY VERSUS COMPETITIVENESS IN ROMANIAN AGRICULTURE. CASE STUDY - Ion, Raluca; Dobre, Iuliana; Soproni, Vasile Darie (Economics of Agriculture, 2019)
The paper investigates the relationships between agricultural productivity, efficiency and farms competitiveness, trying to find out to what extend the farms activity is both efficient and competitive? The research starts from the assumption that a farm can be economically inefficient but competitive, and, reciprocally, an economically efficient farm is not necessarily competitive. A case study of a farm from North-West Romania has been considered. It was found that, although the overall activity of the farm is inefficient in some agricultural years, for certain crops, the farm is competitive in those regarding prices and yields. The analysis goes deeper to compare crops between them and proposes solutions for increasing farms efficiency by replacing inefficient crops to efficient ones, using the method of balance of gains and losses. The results of the research are useful in helping farmers making their decisions regarding the structure of production.